Non-linearity of Metabolic Pathways Critically Influences the Choice of Machine Learning Model - Lo-Thong-Viramoutou, Ophélie; Charton, Philippe; Cadet, Xavier F.; Grondin-Perez, Brigitte; Saavedra, Emma; Damour, Cédric; Cadet, Frédéric (Frontiers in Artificial Intelligence, 2022)
The use of machine learning (ML) in life sciences has gained wide interest over the past years, as it speeds up the development of high performing models. Important modeling tools in biology have proven their worth for pathway design, such as mechanistic models and metabolic networks, as they allow better understanding of mechanisms involved in the functioning of organisms. However, little has been done on the use of ML to model metabolic pathways, and the degree of non-linearity associated with them is not clear. Here, we report the construction of different metabolic pathways with several linear and nonlinear ML models. Different types of data are used; they lead to the prediction of important biological data, such as pathway flux and final product concentration. A comparison reveals that the data features impact model performance and highlight the effectiveness of nonlinear models (e.g., QRF: RMSE=0.021 nmol·min-1 and R2=1 versus Bayesian GLM: RMSE=1.379 nmol·min-1 R2=0.823). It turns out that the greater the degree of non-linearity of the pathway, the better suited a nonlinear model will be. Therefore, a decision-making support for pathway modeling is established. These findings generally support the hypothesis that nonlinear aspects predominate within the metabolic pathways. This must be taken into account when devising possible applications of these pathways for the identification of biomarkers of diseases (e.g., infections, cancer, neurodegenerative diseases) or the optimization of industrial production processes.